Nuotin vierestä soittamisen taito : näkökulmia kenraalibasson olemukseen - Malmgren, Markus (Taideyliopiston Sibelius-Akatemia, 2015)
Markus Malmgren: The Art of Playing between the Notes - Aspects on the Essence of Thorough Bass. Written report presented as part of requirements for the Doctor of Music degree in the Art Study Program. University of the Arts Helsinki, Sibelius Academy, DocMus Doctoral School. Autumn 2015. 184 pages and 11 pages of appendices. My report will look at the function of the organ as a sonorously unifying element in various instrumental and vocal ensembles. This function is apparent in the historical practice of thorough bass, which for that reason serves as the common theme of this work. I discuss organ building, performance practices, playing technique and notation from the point of view of an organist and music director. I question contemporary period instrumental practices in the light of historical sources. But first and foremost, my perspective on thorough bass as a musical phenomenon is broader than the historical, stylistic and theoretical meanings with which it is usually associated. In the 15th century organ building underwent a dramatic development that transformed it into the universal accompaniment instrument. This role - if the capacity of the organ is used in a suitable manner - is still relevant today, regardless of musical style. I therefore take a critical view on contemporary organ pedagogy; its narrow keyboard-centric perspective on the organ and organ playing technique is, on the basis of my research, historically one-sided. Until the beginning of the twentieth century, the work description of an organist was far broader than it is today. The organist played a central role in the public musical sphere, and his tasks usually included the role of composer and conductor in addition to that of performer. Particularly in the realization of liturgical music, the organist would act as principal player of the entire ensemble. Expert knowledge of counterpoint and ability to organize musical resources were considered essential skills for an organist, which is reflected in the qualifications required for a vacancy. For this reason, the study of improvisation and thorough bass was emphasized at the expense of learning solo repertoire in the organist's training. In the 19th century, a general theory of harmony gradually began to supersede thorough bass procedures as the foundation of practical music theory. For organists, composers and conductors, however, thorough bass remained a vital skill well into the twentieth century. As a broad concept and especially as a practical function, thorough bass is not tied to any one musical genre. My study, in fact, indicates that the early 17th century concept of thorough bass is firmly rooted in well established church music practices. The organ was extensively used for the accompaniment of vocal polyphony throughout the 16th century. Therefore there is no reason to consider the concept of thorough bass as a division mark between stylistic periods such as the renaissance and the baroque. 'The thorough bass period' and its better-known twentieth century equivalent 'baroque', are obviously misleading concepts. The respective twentieth century ideologies of the Early Music Revival, the organ culture, and church music may possibly have actually limited general interest in, and expertise of music prior to the 18th century. The main focus of this report is not, however, the period instrument movement as such. The historical practices I have studied can in many ways be relevant in today's increasingly pluralistic musical environment. As ever before 'the art of playing between the notes' unifies musicians across all genres. Keywords: organ, multidisciplinary musicianship, conducting, polyphony, figured bass, performance practice of historical church music, period instruments.

Markus Malmgren: Nuotin vierestä soittamisen taito - näkökulmia kenraalibasson olemukseen. Musiikin tohtorin tutkintoon sisältyvä kirjallinen työ Taideyliopiston Sibelius-Akatemian DocMus-tohtorikoulussa. Kevät 2015. 184 sivua + 11 liitesivua. Tutkin tässä työssä urkujen funktiota erilaisten instrumentaalisten ja vokaalisten kokoonpanojen soinnillisesti yhdistävänä tekijänä. Tämä funktio ilmenee historiallisessa kenraalibassokäytännössä, joka tästä syystä on tutkimukseni keskeinen teema. Pohdin urkujenrakennuksen, esittämiskäytäntöjen, soittotekniikan ja notaation kysymyksiä urkurin ja musiikinjohtajan näkökulmasta. Problematisoin nykyajan periodi-instrumentaalisia käytänteitä historiallisten lähteiden valossa. Ennen muuta kuitenkin tarkastelen kenraalibassoa sen historiallisia, tyylillisiä ja teoreettisia merkityksiä laajempana musiikillisena ilmiönä. Urkujenrakennuksessa tapahtui käänteentekevää kehitystä 1400-luvulla, jolloin uruista tuli universaali säestyssoitin. Tässä roolissa urut - jos niiden ominaisuuksia hyödynnetään tarkoituksenmukaisesti - ovat edelleen täysin ajankohtaiset musiikin tyylilajista riippumatta. Arvioin nykyisen urkurikoulutuksen painotuksia kriittisesti; sen suppean klaveristinen näkökulma urkuihin ja urkujensoittotekniikkaan on tutkimukseni perusteella historiakatsannossa yksipuolinen. Ammattiurkurin toimenkuvahan oli aina 1900-luvun alkuun saakka nykyistä huomattavasti laajempi. Urkurilla oli keskeinen rooli julkisessa musiikkiympäristössä, ja hänen työhönsä liittyi usein niin kapellimestarin kuin säveltäjänkin tehtäviä. Erityisesti liturgisen musiikin toteutuksessa urkuri toimi koko yhtyeen äänenjohtajana. Kontrapunktin hallintaa ja musiikillisten resurssien organisoinnin taitoja pidettiin ensiarvoisina, mikä näkyi urkurin pätevyysvaatimuksissa. Tästä syystä korostuivat urkurien koulutuksessa ei solistinen ohjelmisto vaan kenraalibasso ja improvisointi. Vaikka harmoniaoppi vähitellen 1800-luvun kuluessa otti kenraalibasson paikan musiikinteorian yleisenä lähtökohtana ja perustana, kenraalibasson hallinta säilyi urkureita, säveltäjiä ja kapellimestareita yhdistävänä kompetenssina aina 1900-luvun alkuun saakka. Laajasti ymmärrettynä käsitteenä ja erityisesti käytännön toimintona kenraalibasso ei ole sidoksissa mihinkään musiikin tyyliin. Tutkimukseni viittaakin siihen, että 1600-luvun alussa luotu kenraalibasson käsite liittyi vakiintuneisiin kirkkomusiikin käytäntöihin. Vokaalipolyfoniaa säestettiin varsin yleisesti uruilla kautta 1500-luvun. Näin ollen kenraalibassoa ei ole perusteltua pitää tekijänä, joka erottaa barokin renessanssista. Sellainen käsite kuin "kenraalibassokausi" sekä sen synonyymiksi 1900-luvulla vakiintunut "barokki" johtavat siis mitä ilmeisimmin harhaan. Kysymykseksi asettuukin, ovatko vanhan musiikin liikkeen, urkutaiteen ja kirkkomusiikin 1900-luvulla muotoutuneet ideologiset päämäärät itse asiassa rajoittaneet yleistä kiinnostusta ja sen myötä myös osaamista erityisesti 1700-lukua vanhempaa musiikkia kohtaan. Tämän työni päämäärät eivät kuitenkaan kohdistu periodisoitinkulttuuriin sinänsä: tutkimani historialliset käytänteet voivat olla monella tapaa ajankohtaisia nykyajan yhä useampimuotoisessa ja -sisältöisessä musiikkiympäristössä. "Nuotin vierestä soittamisen taito" yhdistää nimittäin nykyäänkin muusikoita yli kaikkien genrerajojen. Avainsanat: Urut, monialainen muusikkous, musiikinjohto, polyfonia, kenraalibasso, historiallisen kirkkomusiikin käytännöt, periodisoitinkulttuuri.

Markus Malmgren: Konsten att spela mellan noterna - aspekter på generalbasens väsen. Avhandling för musikdoktorsexamen på den konstnärliga linjen vid DocMus-doktorsskolan. Konstuniversitetet, Sibelius-Akademin. Hösten 2015. 184 sidor + 11 bilagssidor. I denna studie undersöker jag orgelns funktion som klangligt förenande element i olika vokala och instrumentala sammansättningar. Denna funktion är utmärkande för historisk generalbaspraxis, varför densamma också utgör det centrala temat i mitt skriftliga arbete. Jag behandlar frågor kring orgelbyggnation, uppföringspraxis, spelteknik och notation från organistens och dirigentens synvinkel. Jag ifrågasätter nutida periodinstrumentala kutymer mot bakgrunden av historiskt källmaterial. Men främst strävar jag efter att vidga begreppet generalbas i förhållande till dess traditionella konnotationer som ett historiskt fenomen, ett stilistisk attribut och ett teoretiskt system. Orgelbyggnationen genomgick ett omvälvande skede på 1400-talet, då orgeln utvecklades till ett universalt ackompanjemangsinstrument. I denna roll är orgeln - om dess potential utnyttjas ändamålsenligt - alltjämt fullt relevant, oberoende av musikalisk genre. Jag granskar kritiskt prioriteringar inom dagens organistutbildning; att man betraktar orgeln ur en snävt klaveristisk synvinkel står enligt min studie i bjärt kontrast med historisk orgelpedagogisk praxis. Yrkesorganistens arbetsbild var ju ända fram till början av 1900-talet betydligt mångsidigare än nuförtiden. Organisten hade en central ställning i det offentliga musikaliska rummet; såväl kapellmästar- som kompositörsrollen ingick i hans tjänsteplikter. Särskilt inom den liturgiska musiken fungerade organisten som primus motor för hela den musikaliska apparaten. Kontrapunktisk expertis och förmåga att administrera musikaliska resurser var av högsta vikt. Därför prioriterades generalbas och improvisation högre än inövande av solistisk repertoar i organistutbildningen. Under 1800-talets gång kom visserligen harmoniläran att så småningom ersätta generalbasen som grund för gemene musikers teoretiska insikter. Generalbasen förblev dock en professionellt förenande länk mellan organister, kompositörer och kapellmästare ända till början av 1900-talet. I begreppets vidaste bemärkelse och i synnerhet som praktisk funktion är generalbasen inte knuten till någon särskild musikstil. Min studie tyder på, att begreppet generalbas, när det skapades i början av 1600-talet, anslöt sig till en väl etablerad praxis: bruket att utnyttja orgeln till att ackompanjera vokalpolyfoni var allmänt utbrett under åtminstone hela 1500-talet. Det är således knappast befogat att betrakta generalbasen som en skiljelinje mellan renässans och barock. Såväl begreppet "generalbasepoken" som den motsvarande benämning som etablerade sig under 1900-talet, "barocken", är alltså uppenbart vilseledande. Möjligen har till och med rent ideologiska motiv hos respektive intressegrupp - periodinstrumentkulturen, orgelkonsten och kyrkomusiken - bidragit till att begränsa både det allmänna och det professionella intresset för historisk uppföringspraxis när det gäller musik från tiden före 1700-talet. Fokus för min studie ligger dock inte på periodinstrumentalism och historisk repertoar i sig: väsentligt är, att de historiska praxis jag utforskat på många sätt kan vara aktuella också i dagens ständigt mer pluralistiska musikkultur. "Konsten att spela mellan noterna" förenar nämligen också idag musiker över alla genremässiga gränser. Nyckelord: orgel, musikalisk multikompetens, dirigering, polyfoni, generalbas, historisk kyrkomusikpraxis, periodinstrumentkultur
Keywords: urut; muusikkous; monialaisuus; johtaminen; musiikki; polyfonia; kenraalibasso; kirkkomusiikki; käytäntö; periodisoittimet; kulttuuri; DocMus